Welfare state transformation between workfare and an enabling state: a comparative analysis - Irene Dingeldey (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2005)
Some scholars of social policy claim that the traditional post war Keynesian Welfare State has been transformed towards a Schumpeterian Workfare State (Jessop 1994, Tor-fing 1999a). Others conceptualise welfare state reform as transformation towards an Enabling (Gilbert/Gilbert 1989), Activating (OECD 1990, Bandemer 2001, Mezger 2000) or Co-operative State (Schmid 1996). All these concepts have in common to be rather normative: While the `Workfare thesis underlines a negative scenario of enforced commodification of welfare state clients, authors proclaiming an activating, enabling or co-operative welfare state highlight the preventive and emancipatory aspects of new welfare state policies. With reference to this controversy the author of the present paper, however, argues that the workfare and the enabling state are not alternative paths of development, but mutually constitutive concepts of welfare state transformation. Evidence for this argument is given by a comparison of activating labour market policies in most divergent Western European welfare states like Denmark, the UK and Germany.Empirical findings indeed confirm that all countries implement a mix of workfare and enabling elements although displaying major variations due to different historical social policy paths. General characteristics of policy transformation are changing forms of governance. These include the reduction of welfare state protection by financial transfers and the increase of social and educational services. The introduction of contractual regulation puts forward individualisation and self responsibility, but also co-operation and co-production between the state and the individual. Seeking clients compliance, however, the state also increases sanctions and coercion. As a result of the reforms an increasing influence of the state on the individuals living conduct is noticed. – – Einige Sozialpolitikforscher proklamieren, dass sich der traditionelle keynesianische Wohlfahrtsstaat der Nachkriegsära zu einem Schumpeterianischen Workfare-Staat wandelt. Andere skizzieren eine Veränderung hin zum befähigenden, aktivierenden oder kooperativen Staat. Allen diese Konzeptionen sind vergleichsweise normativ: Während die Workfare-These ein negatives Szenario des zunehmenden Arbeitszwangs für Wohlfahrtsstaatsklienten betont, werden von den Protagonisten eines aktivierenden, befähigenden oder kooperativen Wohlfahrtsstaates die präventiven und emanzipatorischen Aspekte neuer wohlfahrtsstaatlicher Politik betont. Mit Bezug zu dieser Kontroverse betont die Autorin des vorliegenden Arbeitspapiers, dass es sich bei den Konzeptionen des Workfare-State und des befähigenden Wohlfahrtsstaates nicht um alternative Entwicklungsszenarien handelt, sondern um sich gegenseitig ergänzende Aspekte wohlfahrtsstaatlicher Transformation. Dies wird anhand eines Vergleichs aktivierender Arbeitsmarktpolitik in stark unterschiedlich geprägten westlichen Wohlfahrtsstaaten wie Dänemark, Großbritannien und Deutschland begründet.Die empirischen Ergebnisse bestätigen, dass in allen genannten Ländern ein Mix aus Arbeitszwang und befähigenden Politiken implementiert wird, der sich jedoch je nach historischem Entwicklungspfad der Sozialpolitik unterscheidet. Generelles Kennzeichen der Politiktransformation ist der Wandel von Governance. Dies schließt die Rücknahme wohlfahrtsstaatlicher Sicherung durch den Rückbau finanzieller Transfers und den Ausbau sozialer und bildungsbezogener Dienstleistungen ein. Die Einführung von Kontrakten geht mit der Individualisierung von Leistungen und der Zunahme von Selbstverantwortung der Individuen einher, aber auch mit der Zunahme von Kooperation und Koproduktion zwischen Staat und Individuum. Um die aktive Beteiligung der Sozialstaatsklienten sicherzustellen, nehmen jedoch ebenso sozialstaatlicher Zwang und Sanktionen zu. Als Ergebnis der Reformen ist daher ein zunehmender Einfluss des Sozialstaates auf die individuelle Lebensführung festzustellen.
Keywords: 330; Sozialreform; Workfare; Arbeitsmarktpolitik; Dänemark; Großbritannien; Deutschland